2016
DOI: 10.1016/j.jalz.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference is correlated with poorer cognition in elderly type 2 diabetes women

Abstract: Introduction Waist circumference is associated with type 2 diabetes (T2D) and cognition, yet the relationship between waist circumference and cognition in individuals with T2D is not well understood. Methods We studied the relationship of waist circumference with five cognitive outcomes (executive functioning, language/semantic categorization, attention/working memory, episodic memory, and an overall cognition measure) in 845 cognitively normal elderly with type 2 diabetes (T2D). Results In women, waist ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
(29 reference statements)
3
18
0
Order By: Relevance
“…Other pathways may operate in the subjective age-dementia link. For example, an older subjective age is also associated with higher systemic inflammation (Stephan et al, 2015a), greater metabolic dysregulation and lower pulmonary function (Stephan et al, 2015b) that contribute to higher dementia risk (Heneka et al, 2015; Vidal et al, 2013; West et al, 2016). In addition, individuals who feel older are more vulnerable to stress (Shrira et al, 2016), which amplifies the likelihood of cognitive impairment and dementia (Mah et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways may operate in the subjective age-dementia link. For example, an older subjective age is also associated with higher systemic inflammation (Stephan et al, 2015a), greater metabolic dysregulation and lower pulmonary function (Stephan et al, 2015b) that contribute to higher dementia risk (Heneka et al, 2015; Vidal et al, 2013; West et al, 2016). In addition, individuals who feel older are more vulnerable to stress (Shrira et al, 2016), which amplifies the likelihood of cognitive impairment and dementia (Mah et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Abbatecola et al showed that central adiposity, represented by WC, predicted an increased risk for cognitive decline during a 2‐year follow‐up period in older patients with diabetes. Recently, West et al reported that WC was correlated with lower overall cognition and executive performance in older women with type 2 diabetes. However, there has been no large‐scale cohort study to examine the association of late‐life WC with the incidence of dementia in an older population.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited information pertaining to the contribution of central obesity to cognitive dysfunction in T2DM. Traditional measures of central obesity, namely waist circumference (WC) and waist:hip ratio (WHR), were found to be associated with diminished cognitive performance in older individuals with T2DM . Whether the relationship between central obesity and cognition differs with the degree of general obesity remains unelucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional measures of central obesity, namely waist circumference (WC) and waist:hip ratio (WHR), were found to be associated with diminished cognitive performance in older individuals with T2DM. 9,11 Whether the relationship between central obesity and cognition differs with the degree of general obesity remains unelucidated. In this cross-sectional observational study, we evaluated the association of several traditional and novel measures of central obesity with cognitive function in non-demented multi-ethnic Asians with T2DM, including a stratified analysis by BMI.…”
Section: Introductionmentioning
confidence: 99%